Architecture of African satellite augmentation system (ASAS) for Africa and middle east - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2019)
This paper introduces architecture of African Satellite Augmentation System (ASAS) project designed by African for Africa, with coverage of entire African Continent and Middle East for maritime, land (road and rail) and aeronautical applications. The ASAS network is de facto Regional Satellite Augmentation System (RSAS) as integration component of the Global Satellite Augmentation System (GSAS) employing current and new Satellite Communication, Navigation and Surveillance (CNS) for improved traffic control and management at sea, on land and in the air. This Network also enhances safety and emergency systems, transport security and control of transportation freight, logistics and the security of the crew and passengers onboard transport systems. The current infrastructures of the first generation of Global Navigation Satellite System (GNSS-1) applications are represented by old fundamental solutions for Position, Velocity and Time (PVT) of the satellite navigation and determination systems such as the US GPS and Russian (former-USSR) GLONASS military requirements, respectively. The establishment of Local Satellite Augmentation System (LSAS) and mobile movement guidance and control are also discussed as special infrastructures in seaports, land and airports environments.
Keywords: ASAS; RSAS; GSAS; CNS; GNSS; GPS; GLONAS; LSAS; CMGC; SMGC; LMGC.